'Still out on the street waging this fight': Women irregular workers and industrial action in Korea. (May 2018) - Young, Kim; Broadbent, Kaye
This article reviews the 510-day strike by women irregular workers in the South Korean retail industry, and analyses factors which made a group of women irregular workers, whose employment conditions render them the most marginal employees, to sustain a lengthy struggle despite financial and family pressures. This article argues there are three factors behind the struggle: first their desire to address the employment discrimination and inhumane treatment they faced at work; second their belief that the struggle was larger than just their immediate demands; and third the solidarity and support they received from both the union and full-time colleagues and from the broader community.